The regional system of innovation and regional development - Andreas P. Cornett (European Regional Science Association (ERSA), 2002)
Innovations and the capacity to innovate are crucial factors in the development of a firm and its ability to adapt to changes in the external environment. Growing attention has been paid to the mechanism facilitating innovation in firms, both in large, small and medium-sized enterprises. As a consequence, increasing attention has been on the role of innovation policy in regional development. The purpose of this project is to analyse the linkages between the business advisory systems efforts to promote innovation and the innovative firm with special attention to small and medium sized enterprises. The analysis of this paper deals with entities and relations of the innovative environment. The focal point is the interaction between the analysed business entity and the external environment as a part of a broader network of innovative relations covering intra-firm as well as extra-firm relations and processes. The first part of the paper addresses various concepts of innovation and the role of the advisory system in the creation of a regional innovative business environment. The second part of the paper reports first findings from a survey of manufacturing firms and advisory organisations in Southern Denmark and Northern Germany. The essential objective of this part is to identify the potential of and the crucial obstacles to a proactive regional innovation policy, since previous studies have shown that in particular small firms have difficulties to use the advisory system and the services offered. The final section of the paper summarizes the findings of the questionnaire, and provide a first assessment of how to create a proactive regional development based on literature and the results of the empirical survey. Key-words: Regional system of innovation - Advisory system - business incubators and science parks - R & D programs
Keywords: 330